A sample cell for in situ electric‐field‐dependent structural characterization and macroscopic strain measurements. (1st May 2016) - Hossain, Mohammad J.; Wang, Lijun; Wang, Zhiyang; Khansur, Neamul H.; Hinterstein, Manuel; Kimpton, Justin A.; Daniels, John E.
Abstract : A sample cell for in situ electric‐field‐dependent structural characterization and macroscopic strain measurements is demonstrated. The results show that the macroscopic strain measured using the cell can be directly correlated with the microscopic response of the material obtained from diffraction data. Abstract : When studying electro‐mechanical materials, observing the structural changes during the actuation process is necessary for gaining a complete picture of the structure–property relationship as certain mechanisms may be meta‐stable during actuation. In situ diffraction methods offer a powerful and direct means of quantifying the structural contributions to the macroscopic strain of these materials. Here, a sample cell is demonstrated capable of measuring the structural variations of electro‐mechanical materials under applied electric potentials up to 10 kV. The cell is designed for use with X‐ray scattering techniques in reflection geometry, while simultaneously collecting macroscopic strain data using a linear displacement sensor. The results show that the macroscopic strain measured using the cell can be directly correlated with the microscopic response of the material obtained from diffraction data. The capabilities of the cell have been successfully demonstrated at the Powder Diffraction beamline of the Australian Synchrotron and the potential implementation of this cell with laboratory X‐ray diffraction instrumentation is also discussed.